TICE Afrique ou comment compléter les formations des enseignants en Afrique - Raymonde Moussavou; Karen Ferreira-Meyers; Mireille Essono Ebang; Ana Gainza (Multilinguales)
The article is about TICE Africa, a digital exchange platform aimed at complementing teacher training. Some members are developing new digital skills there. However, thanks to a qualitative exploration of their verbalizations, access to high-speed internet and mastery of the digital tool for all is difficult.